ECIL guidelines for treatment of Pneumocystis jirovecii pneumonia in non-HIV-infected haematology patients - Maschmeyer, Georg; Helweg-Larsen, Jannik; Pagano, Livio; Robin, Christine; Cordonnier, Catherine; Schellongowski, Peter (Journal of antimicrobial chemotherapy, 2016)
The initiation of systemic antimicrobial treatment of Pneumocystis jirovecii pneumonia (PCP) is triggered by clinical signs and symptoms, typical radiological and occasionally laboratory findings in patients at risk of this infection. Diagnostic proof by bronchoalveolar lavage should not delay the start of treatment. Most patients with haematological malignancies present with a severe PCP; therefore, antimicrobial therapy should be started intravenously. High-dose trimethoprim/sulfamethoxazole is the treatment of choice. In patients with documented intolerance to this regimen, the preferred alternative is the combination of primaquine plus clindamycin. Treatment success should be first evaluated after 1 week, and in case of clinical non-response, pulmonary CT scan and bronchoalveolar lavage should be repeated to look for secondary or co-infections. Treatment duration typically is 3 weeks and secondary anti-PCP prophylaxis is indicated in all patients thereafter. In patients with critical respiratory failure, non-invasive ventilation is not significantly superior to intubation and mechanical ventilation. The administration of glucocorticoids must be decided on a case-by-case basis.